Warunki napływu kapitału zagranicznego w Polsce - Stawicka, Magdalena (Conditions for the influx of foreign capital in Poland, 2006)
The purpose of this article is to make a survey of conditions enabling the influx of foreign capital into Poland, to which elements belong: economic, social, political administration - legal. From note on this, that factor administration - legal it is very wide subject, Authoress introduced only three remaining. They to main problems of Polish economy belong first of all the lack of road infrastructure and Lelecommunicational, and also low expenditures on audit and development. For Poland important it is promoting investment and attraction capital to exacting sectors refinancing at present. Thanks to presence of foreign investments, Poland strengthened the position in international conversion trade. Poland should further to create the favourable for foreign investors conditions and to enlarge the inflow of direct foreign investments.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 363-369